Pharmacokinetic interaction of rosuvastatin with artichoke (Cynara scolymus L.) leaf extract in rats - Ahmad M. Al Masalmeh, Eyad Mallah, Kenza Mansoor, Luay Abu-Qatouseh, Feras Darwish El-Hajji, Nasir Idkaidek, Iman Basheti, Israa Haj Issa, Ahmad Z. Al Meslamani, Saba Aws (Journal of Applied Pharmaceutical Science, 2023)
Dyslipidemia is a prevalent disease among the international population that has substantially increased, which can be treated with several hypolipidemic drugs such as rosuvastatin. Artichoke is a plant that is commonly used to treat high levels of cholesterol and lipids in the blood (hyperlipidemia). This study was performed to evaluate the drug-herb interaction due to the simultaneous use of artichoke leaves extract (ALE) with both doses of rosuvastatin. Furthermore, the effect of (ALE) on the pharmacokinetic profile of rosuvastatin in rat plasma was evaluated. Invivo studies were carried out on 56 laboratory rats. Dyslipidemia was induced by intragastric cholesterol intake (2 g/kg) every day for 4 weeks. After inducing dyslipidemia, rats were separated into seven study groups. All treatment protocols were efficacious in curing dyslipidemia, all of which significantly decreased total cholesterol, triglyceride, low-density lipoprotein, and very low-density lipoprotein levels and significantly raised high-density lipoprotein cholesterol (p ≤ 0.05). Moreover, a significant pharmacokinetic interaction was noticed when combining ALE with rosuvastatin on Cmax and Area under the curve (AUC) (p ≤ 0.01) of rosuvastatin along with decreasing its concentration in the serum blood from 755 to 388 ng/ml. All treatment protocols of rosuvastatin, ALE, or their combination and chlorogenic acid had a hypolipidemic activity that altered all lipid profile parameters.
Keywords: Dyslipidemia, cholesterol, artichoke, rosuvastatin